1986
DOI: 10.1073/pnas.83.18.6854
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone-releasing factor stimulates proliferation of somatotrophs in vitro.

Abstract: The mitogenic effect of the hypothalamic peptides growth hormone-releasing factor (GRF) and somatostatin on cultured growth hormone (GH)-producing cells (somatotrophs) was studied. Using autoradiographic detection of [3H]thymidine uptake and immunocytochemical identification of GH-producing cells, we show that 5 nM GRF causes a 20-fold increase in the percentage of somatotrophs labeled with [3H]thymidine. The total number of somatotrophs in GRFtreated cultures was increased by 60%. Somatostatin had no measurab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
1
3

Year Published

1988
1988
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(121 citation statements)
references
References 21 publications
3
114
1
3
Order By: Relevance
“…It is also possible that low rGH levels in our transgenic rats were due to inhibition of somatotoroph proliferation. GRF stimulates proliferation of somatotorophs, and this mitogenic effect is partially inhibited by somatostatin [29]. It will be worth examining the expression of SRIF and GRF in our transgenic rats to elucidate the precise mechanisms of endogenous rGH suppression.…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that low rGH levels in our transgenic rats were due to inhibition of somatotoroph proliferation. GRF stimulates proliferation of somatotorophs, and this mitogenic effect is partially inhibited by somatostatin [29]. It will be worth examining the expression of SRIF and GRF in our transgenic rats to elucidate the precise mechanisms of endogenous rGH suppression.…”
Section: Resultsmentioning
confidence: 99%
“…These two hypothalamic peptides are released from nerve endings in the median eminence and reach the anterior pituitary via the hypophysial-portal circulation [1][2][3]. Moreover, it has been reported that GHRH and SRIF regulate mitotic activities of GH-producing cells and that the effect of GHRH is possibly mediated by cyclic AMP [4]. A hexapeptide, His-D-Trp-AlaTrp-D-Phe-Lys-NH2…”
Section: Somatostatin Pituitary Cellmentioning
confidence: 99%
“…The primary function of GHRH is to stimulate GH synthesis and secretion from anterior pituitary somatotrophs via specific interaction with its receptor, GHRH-R (5). In addition, GHRH activates cell proliferation, cell differentiation, and growth of somatotrophs (6)(7)(8). There are many other reported activities of GHRH such as modulation of appetite and feeding behavior, regulation of sleeping (9,10), control of jejunal motility (11), and increase of leptin levels in modest obesity (12).…”
mentioning
confidence: 99%